Public Participation in Environmental Issues in Bandung City - Ike Junita Triwardhani; Ema Khotimah Kennedy (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
In the contemporary era of globalization, public participation has emerged as a pivotal element in the management of environmental issues.  The city of Bandung, in particular, is confronted with a myriad of environmental challenges that necessitate the active involvement of the public. This research endeavors to explore the extent of public participation and its influencing factors in the context of environmental issues in Bandung.  Specifically, the objective is threefold: first, to identify forms of public participation; second, to understand the role of stakeholders; and third, to evaluate the effectiveness of communication channels.  The study also aims to provide recommendations to improve public involvement in environmental management. The research method is a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis, involving various stakeholders, including NGOs, environmental experts, and the general public. The results show that public participation in Bandung is still limited and often formalistic.  Despite the existence of diverse communication channels, the level of public awareness and engagement in environmental issues remains inadequate. Stakeholders, comprising government entities and NGOs, play a pivotal role in fostering enhanced participation. This study posits that to augment public participation in the management of environmental issues in Bandung City, a more inclusive and strategic approach is imperative. Recommendations are put forth to refine communication channels and cultivate public awareness, thereby facilitating active contribution to environmental decision-making.